2013
DOI: 10.1051/0004-6361/201321508
|View full text |Cite
|
Sign up to set email alerts
|

The Monitor Project: stellar rotation at 13 Myr

Abstract: Aims. We aim at constraining the angular momentum evolution of low-mass stars by measuring their rotation rates when they begin to evolve freely towards the zero-age main sequence (ZAMS), i.e., after the disk accretion phase has stopped. Methods. We conducted a multisite photometric monitoring of the young open cluster h Persei, which has an age of ∼13 Myr. The observations were done in the I-band using four different telescopes, and the variability study is sensitive to periods from less than 0.2 day to 20 da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 58 publications
12
116
0
Order By: Relevance
“…Figure 8 shows the variation of the coupling timescales upon angular velocity as derived from our parametric models. A power-law fit yields τ c−e ∝ 1/Ω [0.4−0.6] conv , while a previous study by Moraux et al (2013) of PMS and ZAMS clusters suggested τ c−e ∝ 1/Ω. While these parametric slopes are at variance with the analytical predictions, they nevertheless agree with the expected trend for a shorter coupling timescale in faster rotators.…”
Section: Core-envelope Decoupling and The Timescale For Angular Momensupporting
confidence: 57%
See 1 more Smart Citation
“…Figure 8 shows the variation of the coupling timescales upon angular velocity as derived from our parametric models. A power-law fit yields τ c−e ∝ 1/Ω [0.4−0.6] conv , while a previous study by Moraux et al (2013) of PMS and ZAMS clusters suggested τ c−e ∝ 1/Ω. While these parametric slopes are at variance with the analytical predictions, they nevertheless agree with the expected trend for a shorter coupling timescale in faster rotators.…”
Section: Core-envelope Decoupling and The Timescale For Angular Momensupporting
confidence: 57%
“…Most stellar quantities increase for higher mass stars (i.e. the stellar radius and moment of inertia, the moment of inertia of the radiative core, as well as its radius and 1 We thus rejected M 50-5-1624, -3-1468, -3-464, -7-7623, -3-5840, -7-5624, -5-2673, -3-7334, -3-2531, -6-1574, -4-2077, -4-4939, and -8-6076 from M 50 ), N2362-2-6989, and N2362-5-4947 from NGC 2362, #11041 (number from Hillenbrand 1997) from ONC, and #494 (number from Moraux et al 2013) from h Per, and #3245 (number from Littlefair et al 2010) from CepOB3b. 2 We thus rejected 1SWASP J083722.23+201037.0 (KW 30) and 1SWASP J084005.72+190130.7 (KW 256) in Praesepe (Delorme et al 2011).…”
Section: Structural Stellar Evolutionmentioning
confidence: 99%
“…Our results agree reasonably well with these observations. However, at 12.1 Myr, our simulation does not reproduce the bimodal rotational distribution of h Per cluster members, which exhibit one peak at ≤1 day and another at 3−7 days (Moraux et al 2013). Instead, the period distribution of diskless stars in our simulation moves to shorter periods as a whole by an age of 12.1 Myr with a single peak at P peak ∼ 2 days.…”
Section: Model M1mentioning
confidence: 65%
“…Squares represent Class II stars, crosses Class III stars. At 13 Myr, the specific angular momenta of h Per members from Moraux et al (2013) are plotted as gray diamonds.…”
Section: Period -Mass Relationshipmentioning
confidence: 99%
“…In particular, the advent of large surveys designed to search for extrasolar planets has yielded very large data sets of stellar rotation periods as a natural byproduct for both field stars (Hartman et al 2011) and open clusters stars. Examples of the latter include the extensive MONITOR program (Aigrain et al 2007) (see Moraux et al 2013, for the most recent results), the SuperWASP data for the Hyades and Praesepe (Delorme et al 2011) and the large (Hartman et al 2009(Hartman et al , 2010 M37 and Pleiades data sets. The Kepler and CoRoT missions reach lower amplitudes and can detect stars with longer rotation periods, pushing stellar rotation measurements into the solar regime (Basri et al 2011;Garcia et al 2014;Walkowicz and Basri 2013;Nielsen et al 2013;Reinhold et al 2013;McQuillan et al 2014).…”
Section: Stellar Rotation and Spin Downmentioning
confidence: 99%